Testosterone deficiency syndrome and cardiovascular health: An assessment of beliefs, knowledge and practice of general practitioners and cardiologists in Victoria, BC - Wallis, Christopher; Nelson, Hilary L.; Pommerville, P. J. (Canadian Urological Association Journal, 2014)
Introduction: Testosterone deficiency syndrome (TDS) has been shown to be an independent cardiovascular risk factor and a predisposing factor for metabolic syndrome. As general practitioners and cardiologists primarily care for these patients, we sought to assess their knowledge, beliefs and practice patterns with respect to TDS and cardiac health. Methods: We distributed a questionnaire to all 20 cardiologists and a cohort of 128 family practitioners in Victoria, British Columbia. Of the 13 questions, 10 assessed knowledge and beliefs on TDS and 3 assessed current practice patterns. Results: Most respondents believed that TDS is a medical condition (66.7%) and could negatively affect body composition (62%), buta similar majority was unsure whether it was a cardiac risk factor (66.7%). While most believed that testosterone replacement therapy (TRT) could improve exercise tolerance (62%), most were unsure if it was beneficial in cardiac patients. Cardiologists were significantly less likely to believe that TRT was beneficial in preventing recurrent myocardial infarction and improving myocardial perfusion (p = 0.0133, 0.00186, respectively). The vast majority (88%) did not screen cardiac patients for TDS. If a patient was identified as having TDS, only 10% of those surveyed would refer these patients to a urologist. Conclusion: Despite its prevalence in cardiac patients, TDS is not well-understood by general practitioners and cardiologists; they lack knowledge on its deleterious cardiovascular effects. In their role as men’s health advocates, urologists should educate our colleagues regarding the correlation between TDS and cardiovascular mortality and risk factors. Limitations of this study include small sample size and restricted geographic scope.